Change management in Indo-Japanese cross-cultural collaborative contexts: Parallels between traditional Indian philosophy and contemporary Japanese management. Issue 1 (12th February 2018) - Ashta, Ashok; Stokes, Peter; Hughes, Paul
Abstract : Purpose: Within the globalized commercial context, Japanese business activity in India has increased significantly. The purpose of this paper is to highlight common attitudinal traits that would facilitate orientation of Indian executives towards Japanese management methods through, for instance "reverse adaptation", using an approach other than cultural dimensions that have emerged in recent decades and consider how these play out in change management contexts. Design/methodology/approach: A literature review was undertaken which found significant parallels between traditional Indian philosophy and modern Japanese management methods, inter alia long-term orientation, equanimity and Nemawashi (pre-arranged participative decision making) and shared spiritual dimensions. The paper employed a methodology of participant observation and semi-structured interview approaches contextualized through lived experience methodology (Van Manen, 2015 ). These events are described and analysed narratively using a blend of qualitative participant observation and reflexive critical incident review. Findings: The findings, by examining the confluence of Indian and Japanese management, provide an innovative avenue of research and theory for change management. Research limitations/implications: The research employs an inductive methodology which employs vignettes to examine Indo-Japanese contexts. The limits to generalization are recognized within the study. The paper offers important implications on Indo-Japanese collaboration and change management. Practical implications: These findings have important practical implications for Indian and Japanese managers who will be able to engage better within the dynamics of the Japanese work environment in Japanese subsidiaries in India. These same insights could also potentially facilitate wider examples of working in Japanese environments, either in Japan or outside Japan. At a more general level, the findings are relevant to all foreign investors in India for enhanced employee engagement by providing insights into spiritual values of Indian managers and their impact on change management situations. Social implications: There is emerging research on how traditional Indian philosophy tenets can be found in modern (western) management. This paper provides reasons, based in the extant literature, to believe that modern Japanese methods can trace their origin in Buddhist Indian philosophical thought and offer important implications for managing change. Originality/value: The paper offers in-depth original insights into Indo-Japanese collaborative contexts.